(3TQhW GdEbdGY GdEbJUGOj aj GdLRGFQ (B((3GdLRA GdChd(B)s - (3HhYHOdj(B, (3jGSjfs ((3GdLRGFQs (3OGQ CLjGd GdQbej s, 2023)
(3jJVe gPG GdcJGH Ydi GdEWGQ GdfXQj ddEbdGY GdGbJUGOj(B: (3GdGbdGY GdGbJUGOj hGdJCUjd GdfXQj dg, YbjGJ JMbjb GdGbdGY GdGbJUGOj, eJWdHGJ JMbjb JMbjb GdGbdGY GdGbJUGOj, GSJQGJjLjI GdJfejI GdGbJUGOjI, GdGSJKeGQ aj GdehGQO GdHTQjI(B: (3QCS GdeGd GdHTQj,QCS GdeGd GdacQj, QCS GdeGd GdeYQaj, GdGbdGY GdGbJUGOj aj Xd GdGSJKeGQ aj GdehGQO GdHTQjI,, GdGSJKeGQ GdCLfHj hGdGSJKeGQ GdeMdj(B:(3GdGSJKeGQGJ GdCLfHjI GdeHGTQI, GdGSJKeGQ GdeMdj, GdJfhjY GdGbJUGOj(B: (3GdGWGQ GdfXQj ddJfhjY GdGbJUGOj, CgejI hVQhQI GdJfhjY GdGbJUGOj, VQhQIGdJfhjY GdGbJUGOj dJMbjb GdEbdGY hGfYcGSGJg hSdHjGJg, GdJMhd GdWGbhj(B: (3GdUfGYI GdfaWjI, GdZGR GdWHjYj, GdaMe GdMLQj(B: (3GBKGQ GdSdHjI ddWGbGJ GdJbdjOjI, GdWGbGJ GdeJLOOI, GdWGbGJ GdeJLOOI hJMOjGJ GdGbdGY GdGbJUGOj, GbJUGO GdeYQaI(B:(3GdeDSSGJ GdfGTFI, eSGgeI GdeDSSGJ GdfGTFI aj JMbjb GdEbdGY GdGbJUGOj, hGbY GdeDSSGJ GdfGTFI aj GdLRGFQ,GSJQGJjLjI JWhjQ GdeDSSGJ GdfGTFI aj GdLRGFQ(B.s
Keywords: (3GdJfejIs; (3GdehGQO GdGbJUGOjIs; (3GdehGQO GdHTQjIs; (3Gdfeh GdEbJUGOjs